Problem-based learning in the English language classroom - Othman, Normala; Ahamed Shah, Mohamed Ismail (Canadian Centre for Science and Education, 2013)
The purpose of this study was to investigate the effects of the problem-based learning approach (PBL) on students in language classes in two areas: course content and language development. The study was conducted on 128 students, grouped into the experimental and control groups, and employed an experimental research design. The syllabus, textbook, and instructor were controlled for both groups. The findings of the study showed that in terms of course content, both groups improved but in terms of language the PBL group showed more improvements. The PBL group showed improvements in the post-writing test, that is, their essays were richer in terms of support and arguments for each point, while the non-PBL did not show much difference in their post-writing test. This indicates that students could still acquire the course content with minimal content instruction. The limitations of the study and suggestions for further research are offered at the end of the paper. Keywords: Problem-Based Learning, traditional approaches, Content-Based Instruction, proficiency